Factors Affecting Cost Performance Completion On Toll Road Projects With Turnkey Contracts - Muhammad F. A. Bakhri; I P. A. Wiguna (Institut Teknologi Sepuluh Nopember (ITS), 2025)
Currently, the implementation of turnkey contracts has recently gained significant attention due to several advantages, such as shorter construction durations, improved construction quality, and reduced overall project costs. However, compared to the traditional Design-Bid-Build (DBB) method, the higher degree of uncertainty in turnkey projects introduces substantial risks, particularly for contractors. Project success in the construction industry is commonly evaluated based on cost performance relative to the planned budget. This study aims to identify and analyze the key variables influencing cost performance in toll road projects delivered through turnkey contracts. A quantitative research approach was applied using Structural Equation Modeling (SEM) with Partial Least Squares (PLS).The study involved 60 respondents representing service providers, ranging from general managers to administrative staff, who were directly engaged in toll road projects using turnkey contracts. Data were collected through structured questionnaires and interviews. The results indicate that contract conditions have the most significant positive impact on cost performance, with a path coefficient of 0.421, influenced by the field conditions variable. Variations in contract conditions or Contract Change Orders (CCOs) were found to significantly affect cost performance. Therefore, identifying potential risks to field conditions and conducting detailed field investigations are critical to maintaining cost control and ensuring project success.